2013
DOI: 10.1177/001440291307900405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Picture Prompts Delivered by a Video iPod on Pedestrian Navigation

Abstract: Transportation access is a major contributor to independence, productivity, and societal inclusion for individuals with intellectual and developmental disabilities (IDD). This study examined the effects of pedestrian navigation training using picture prompts displayed through a video iPod on travel route completion with 4 adults with IDD. Results indicated a functional relation between picture prompts on the video iPod and pedestrian navigation skills to and from various locations. Maintenance data indicated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 22 publications
0
56
0
2
Order By: Relevance
“…Another study concluded that using iPhones to send video captions when participants were lost was an effective strategy to help them find their way back home (Purrazzella & Mechling, 2013). Similarly, Kelley, Test and Cooke (2013) showed that the use of picture prompts with iPods for pedestrian navigation had a positive effect on travel route completion for people with ID (Kelley et al, 2013). A study has suggested that the combination of some forms of VBI, such as video modeling with iPods, has proven to be a useful strategy to teach communication skills (van der Meer et al, 2011) to people with ID.…”
Section: Mobile Technologies For People With Idmentioning
confidence: 99%
“…Another study concluded that using iPhones to send video captions when participants were lost was an effective strategy to help them find their way back home (Purrazzella & Mechling, 2013). Similarly, Kelley, Test and Cooke (2013) showed that the use of picture prompts with iPods for pedestrian navigation had a positive effect on travel route completion for people with ID (Kelley et al, 2013). A study has suggested that the combination of some forms of VBI, such as video modeling with iPods, has proven to be a useful strategy to teach communication skills (van der Meer et al, 2011) to people with ID.…”
Section: Mobile Technologies For People With Idmentioning
confidence: 99%
“…Researchers suggest that mobile devices can help students with disabilities live as independently as possible by mastering skills such as finding direction and using public transportation (Cihak, Fahrenkrog, Ayres, & Smith, 2010;Kelley, Test, & Cooke, 2013;.…”
mentioning
confidence: 99%
“…Using a multiple probe across participants design, researchers found that the video iPod was effective at facilitating independent pedestrian travel in students with ID with one participant continuing to navigate independently for 232 days during the maintenance phase. Mechling andSeid (2011), Cihak et al (2010), and Kelley et al (2013) incorporated the use of handheld devices (i.e., PDA or video iPod) to improve independence and travel skills. However, each of these interventions lacked spontaneity and required prior planning.…”
mentioning
confidence: 99%
“…Kelley et al (2013) concluded that both teachers and students would expect to realize the outcome and the acquired value after the teaching and learning. The evaluation of understanding and value of such outcome was instructional assessment, in which the teaching activities contained the teaching of teachers and the learning of students.…”
Section: Cognitive Loadmentioning
confidence: 99%